Design and real time implementation of single phase boost power factor correction converter - Bouafass, A.; Rahmani, L.; Mekhilef, Saad (Elsevier, 2015)
This paper presents a real time implementation of the single-phase power factor correction (PFC) AC-DC boost converter. A combination of higher order sliding mode controller based on super twisting algorithm and predictive control techniques are implemented to improve the performance of the boost converter. Due to the chattering effects, the higher order sliding mode control (HOSMC) is designed. Also, the predictive technique is modified taking into account the large computational delays. The robustness of the controller is verified conducting simulation in MATLAB, the results show good performances in both steady and transient states. An experiment is conducted through a test bench based on dSPACE 1104. The experimental results proved that the proposed controller enhanced the performance of the converter under different parameters variations. (C) 2014 ISA. Published by Elsevier Ltd. All rights reserved.